Влияние автономного инвертора напряжения с синусоидальной широтно-импульсной модуляцией на устойчивость системы электропривода - Денисов, Ю.А. (Технічна електродинаміка, 2012)
A method for calculating conditions subharmonic stable AC systems, taking into account the discrete of voltage autonomous inverter with sinusoidal PWM based on which the stable area of AC engine drive.